Enhanced Photocatalytic Activity of MIL-125 by Post-Synthetic Modification with Cr-III and Ag Nanoparticles - Abdelhameed, Reda M.
NH2-MIL-125, [Ti8O8(OH)(4)(bdc-NH2)(6)] (bdc(2-) = 1,4-benzene dicarboxylate) is a highly porous metal-organic framework (MOF) that has a band gap lying within the ultraviolet region at about 2.6 eV. The band gap may be reduced by a suitable post-synthetic modification of the nanochannels using conventional organic chemistry methods. Here, it is shown that the photocatalytic activity of NH2-MIL-125 in the degradation of methylene blue under visible light is remarkably augmented by post-synthetic modification with acetylacetone followed by Cr-III complexation. The latter metal ion extends the absorption from the ultraviolet to the visible light region (band gap 2.21 eV). The photogenerated holes migrate from the MOF's valence band to the Cr-III valence band, promoting the separation of holes and electrons and increasing the recombination time. Moreover, it is shown that the MOF's photocatalytic activity is also much improved by doping with Ag nanoparticles, formed in situ by the reduction of Ag+ with the acetylacetonate pendant groups (the resulting MOF band gap is 2.09 eV). Presumably, the Ag nanoparticles are able to accept the MOF's photogenerated electrons, thus avoiding electron-hole recombination. Both, the Cr-and Ag-bearing materials are stable under photocatalytic conditions. These findings open new avenues for improving the photocatalytic activity of MOFs.